ANALISIS PROFITABILITAS DAN LEVERAGE TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Tala, Olifia; Karamoy, Herman (Universitas Sam Ratulangi, 2017)
This study aimed to analyze the profitability and leverage to earnings management. The population of this study is chemical and basic industry sectors manufacturing companies who were registered in Indonesian Stock Exchange from 2012 to 2015. 14 companies in chemical and basic industry sectors manufacturing companies category was used as sample, conducted by using purposive sampling method. Data were analyzed using multiple linear regression analysis with SPSS version 24. The results showed that profitability affects significantly, and leverage have no significant effects on earnings management.Â Keywords: Profitability, Leverage, Earnings Management.